Principle and validation of modified hysteretic models for magnetorheological dampers. (7th July 2015) - Bai, Xian-Xu; Chen, Peng; Qian, Li-Jun
Abstract: Magnetorheological (MR) dampers, semi-active actuators for vibration and shock control systems, have attracted increasing attention during the past two decades. However, it is difficult to establish a precise mathematical model for the MR dampers and their control systems due to their intrinsic strong nonlinear hysteretic behavior. A phenomenological model based on the Bouc–Wen model can be used to effectively describe the nonlinear hysteretic behavior of the MR dampers, but the structure of the phenomenological model is complex and the Bouc–Wen model is functionally redundant. In this paper, based on the phenomenological model, (1) a normalized phenomenological model is derived through incorporating a 'normalization' concept, and (2) a restructured model, also incorporating the 'normalization' concept, is proposed and realized. In order to demonstrate this, a multi-islands genetic algorithm (GA) is employed to identify the parameters of the restructured model, the normalized phenomenological model, and the phenomenological model. The performance of the three models for describing and predicting the damping force characteristics of the MR dampers are compared and analyzed using the identified parameters. The research results indicate that, as compared with the phenomenological model and the normalized phenomenological model, (1) the restructured model can not only effectively decrease the number of the model parameters and reduce the complexity of the model, but can also describe the nonlinear hysteretic behavior of MR dampers more accurately, and (2) the meanings of several model parameters of the restructured model are clearer and the initial ranges of the model parameters are more explicit, which is of significance for parameter identification.